2017
DOI: 10.4102/curationis.v40i1.1715
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotional intelligence and organisational support on work stress of nurses in Ibadan, Nigeria

Abstract: BackgroundUniversally, nurses have been reported to be a group at high risk of workplace stress. However, nurses’ responses to stressful situations at work could be the outcomes of individual differences and organisational factors.ObjectivesWe examined the independent and joint contributions of four dimensions of emotional intelligence and perceived organisational support in work stress of nurses in a teaching hospital in Nigeria.MethodsThe study was a cross-sectional survey research design, which selected 228… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…Supportive workplace environment could help nurses to be more engaged in nursing work and reduce negative emotions. Lawal and Idemudia () found that perceived organizational support contributed significantly in explaining the level of work stress among nurses. Patrick and Laschinger () found that organizational support was positively related to nurse satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Supportive workplace environment could help nurses to be more engaged in nursing work and reduce negative emotions. Lawal and Idemudia () found that perceived organizational support contributed significantly in explaining the level of work stress among nurses. Patrick and Laschinger () found that organizational support was positively related to nurse satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, EI does not operate in a vacuum, but interacts in a bidirectional manner with the environment. For example, multiple authors identified organizational factors including organizational infrastructure, organizational justice and relationships with nurse leaders (Cheng, Huang, Lee, & Ren, 2012;Lawal & Idemudia, 2017) as impacting nurses' EI.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational burnout is defined as mental and physical fatigue and interpersonal alienation caused by chronic work stress that renders workers unable to maintain work functions (Chao, Shih, & Hsu, 2016). This is relevant to nursing as the literature indicates that the high demands of the job have increased the levels of burnout and turnover, creating a shortage of nursing staff across many countries (Hong & Lee, 2016;Karimi, Cheng, Bartram, Leggat, & Sarkeshik, 2015;Lawal & Idemudia, 2017).…”
Section: Importance In Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention that nurses experience stress within their work environment when they accept that job load outweighs their abilities 31) . Therefore, they look for assistance from the external sources to deal with the stress.…”
Section: Social Supportmentioning
confidence: 99%